DIFFERENSIASI PATTY BERBAHAN DASAR UMBI TALAS SEBAGAI OLEH-OLEH KHAS KOTA BOGOR - Maya Dianti, - (2021)
Taro tubers are very easy to find, because they thrive in Indonesia. Therefore, in this study, the raw material for taro tubers was taken as the main ingredient in the experiment of making vegetarian patties. Taro tubers are used as the basic ingredient of a mixture in the process of making patty products, the use of taro tubers as an ingredient in making this patty aims to maintain the existence of taro tubers as souvenirs characteristic of the city of Bogor, and maintain local behavior. The method in this study uses experimental methods and product quality testing by conducting organoleptic tests to expert panelists. The taro-based patty product sample has 4 recipe formulations that will be tested. Furthermore, for a better standard recipe, it will be used as a standard recipe for making Patty and the stages of calculating the selling price, packaging and labeling and formulating marketing strategies will be carried out. Keywords: Product Differentiation, Taro Bulbs, Artificial Meat, Patty